Benchmarking SCM performance and empirical analysis: a case from paint industry - Pratima Mishra; Rajiv Kumar Sharma (Logistics Research, 2014)
The real challenge for managers is to develop and implement a suitable supply chain performance framework that not only helps in making right decisions but also facilitates the benchmarking of their internal supply chain. The main purpose of this study was to develop a framework based on the performance metrics such as (1) total length of the supply chain, (2) supply chain inefficiency ratio and (3) supply chain working capital productivity. Case study approach is used to benchmark the SCM performance of two paint companies. Further, in order to examine the relationship between SCM practices and SCM performance measures, an empirical analysis has been done by formulating research hypothesis. Results show strong support for linkage between SCM practices and selected performance metrics.
Keywords: 650; Supply chain; SCM performance; Benchmark; SCM practices